1909 W.Va. Acts 59, ch. 2, art. 4, § 7. - (:unkn) unknown (My University, 1909)
[T]o regulate or prohibit the keeping of gun powder and other combustible or dangerous articles[.]
Keywords: GUNPOWDER - STORAGE